Topical 5-aminolevulinic acid photodynamic therapy for actinic keratosis increases skin elasticity and hydration - Li-Yi Chan; Wei-En Wang; Ro‑Wei Wu; Jen-Hung Wang; Pin-Yu Chen; Chung‑Hsing Chang (Photodiagnosis and Photodynamic Therapy)
Introduction: Photodynamic therapy (PDT) is a field-directed strategy to manage multiple actinic keratosis (AK) lesions. During the course of PDT, AK has been found to regress; meantime, lentigines, roughness, and fine lines advance on the photoaged skin. In this study, we adopted a noninvasive biophysical platform MPA580 to analyze skin indices of aging, including elasticity, hydration, sebum, transepidermal water loss (TEWL), melanin, erythema, and pH value. We aimed to provide additional quantitative evidence showing that PDT, used in a standard therapeutic regimen that is known to ameliorate AK, can also have significant anti-photoaging effects in a population of older adults with type III-IV skin. Materials and methods: Eighteen volunteers, 12 males and 6 females, mean age 74 years, histopathologically diagnosed with AK were included. Two sessions of PDT were conducted with a 4-week interval. The photosensitizer, 10 % aminolevulinic acid (Ameluz®) was applied to the whole face with occlusion for 2 h, and the whole face was irradiated with a 630-nm light source for 26 min at a mean light dose of 78 J/cm2. Skin biophysical assessments were sequentially performed at four time points. The first was 1 day before the first PDT, the second was 4 weeks after the baseline, the third was 8 weeks after the baseline, and the 4th was 12 weeks after the baseline. Results: Cheek elasticity significantly improved at weeks 4th and 8th (p = 0.006 and 0.002, respectively). Cheek hydration significantly increased at the 4th week (p = 0.018). No significant changes were observed in terms of cheek TEWL, melanin, erythema, sebum and pH values, and all parameters on the forehead and nose tip. Discussion: Topical PDT improves skin hydration and elasticity. It is a promising strategy for photorejuvenation for people aged >70 years. Future studies using large cohorts and long follow-up duration should be conducted to validate our results.